Pulsed Electromagnetic Field Stimulation of Bone Healing and Joint Preservation: Cellular Mechanisms of Skeletal Response. (May 2020) - Cadossi, Ruggero; Massari, Leo; Racine-Avila, Jennifer; Aaron, Roy K.
Abstract : The US FDA has approved pulsed electromagnetic fields (PEMFs) as a safe and effective treatment for nonunions of bone. Despite its clinical use, the mechanisms of action of electromagnetic stimulation of the skeleton have been elusive. Recently, cell membrane receptors have been identified as the site of action of PEMF and provide a mechanistic rationale for clinical use. This review highlights key processes in cell responses to PEMF as follows: (1) signal transduction through A2A and A3 adenosine cell membrane receptors and (2) dose-response effects on the synthesis of structural and signaling extracellular matrix (ECM) components. Through these actions, PEMF can increase the structural integrity of bone and cartilage ECM, enhancing repair, and alter the homeostatic balance of signaling cytokines, producing anti-inflammatory effects. PEMFs exert a proanabolic effect on the bone and cartilage matrix and a chondroprotective effect counteracting the catabolic effects of inflammation in the joint environment. Understanding of PEMF membrane targets, and of the specific intracellular pathways involved, culminating in the synthesis of ECM proteins and reduction in inflammatory cytokines, should enhance confidence in the clinical use of PEMF and the identification of clinical conditions likely to be affected by PEMF exposure.